2022
DOI: 10.12659/msm.937504
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Practical Screening Tool to Predict Sarcopenia in Patients on Maintenance Hemodialysis

Abstract: Background Sarcopenia is a common complication in maintenance hemodialysis (MHD) and can increase patient hospitalization and mortality. No simple and reliable tools to identify sarcopenia exist. We aimed to develop a screening tool to predict MHD patients at high risk for sarcopenia. Material/Methods This cross-sectional study included 589 and 216 MHD patients for training and validation sets, respectively. We used diagnostic criteria developed by the Asian Working Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The ABC 2 -Screener showed useful discriminative and calibration performance in external validation, particularly for web-based programmes. The discriminative ability of the ABC 2 -Screener in external validation was excellent for both the point-scoring system and web-based programme (0.9149 and 0.9708, respectively) and equal to or superior to those of the aforementioned clinical prediction models (especially the web-based programme) (12)(13)(14)17). The external validation calibration of our tool showed a good fit across low to high predicted risk for the web-based programme while the intermediate predicted risk was underestimated for the point score system.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The ABC 2 -Screener showed useful discriminative and calibration performance in external validation, particularly for web-based programmes. The discriminative ability of the ABC 2 -Screener in external validation was excellent for both the point-scoring system and web-based programme (0.9149 and 0.9708, respectively) and equal to or superior to those of the aforementioned clinical prediction models (especially the web-based programme) (12)(13)(14)17). The external validation calibration of our tool showed a good fit across low to high predicted risk for the web-based programme while the intermediate predicted risk was underestimated for the point score system.…”
Section: Discussionmentioning
confidence: 95%
“…The MUAC measurements, which can be useful in predicting sarcopenia in the general population (31), are typically measured in the non-dominant arm. However, MUAC measurements in patients undergoing haemodialysis are generally performed on the side without vascular access which does not necessarily correspond to the dominant side; thus, MUAC measurements may differ between the dominant and non-dominant sides (13,32). Consequently, this may lead to misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the risk factors for sarcopenia in Chinese MHD patients have been reported extensively, but some with controversial conclusions. 17 18 For example, Du W et al [17]. reported that albumin was associated with sarcopenia(OR 0.87, 95%CI 0.74 to 1.02).…”
Section: Introductionmentioning
confidence: 99%